2018
DOI: 10.1002/jib.511
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of tropical fruit wines

Abstract: Fermentation of different fruits offers diverse flavours, aromas and colours as well as possible benefits from dietary fibre, vitamins and phenolic compounds. In this work, wines were prepared from dragon fruit from the cactus cagaita, the grape‐like berry from jabuticaba and the yellow berry from the cactus pitaya. Fruit wines from cagaita, jabuticaba and pitaya were analysed for volatile compounds, phenolic content and antioxidant capacity (DPPH and FRAP). The cagaita wine showed the highest ability to scave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Differences in winemaking, including our 0.25:1 dilution, along with the absence of ascorbic acid-mediated phenolic augmentation in our method, probably account for this large discrepancy. In strong contrast to our findings, De Souza et al (2018) reported a total phenolic value of 28 mg GAE L À1 for a dragon fruit wine prepared by 1:1 dilution of the must and no pectinase addition, followed by post-ferment diatomaceous earth and cellulose filtration, centrifugation and further filtration. That finding probably resulted from the removal of phenols bound to polysaccharide mucilage (Taira et al, 1997).…”
Section: Total Phenolicscontrasting
confidence: 99%
“…Differences in winemaking, including our 0.25:1 dilution, along with the absence of ascorbic acid-mediated phenolic augmentation in our method, probably account for this large discrepancy. In strong contrast to our findings, De Souza et al (2018) reported a total phenolic value of 28 mg GAE L À1 for a dragon fruit wine prepared by 1:1 dilution of the must and no pectinase addition, followed by post-ferment diatomaceous earth and cellulose filtration, centrifugation and further filtration. That finding probably resulted from the removal of phenols bound to polysaccharide mucilage (Taira et al, 1997).…”
Section: Total Phenolicscontrasting
confidence: 99%
“…These wines are an important source of bioactive compounds highlighting phenolic compounds, amino acids, minerals, vitamins, and carotenoid pigments. Most bioactive compounds present in the fruit and rice are bonded to insoluble plant compounds, and during the winemaking process, many of them are liberate and can be transferred into the wine, reducing the risks of certain diseases (Amidžić et al., 2016; Pantelic et al., 2014; Shahidi, 2009; Shen et al., 2010, 2011; De Souza et al., 2018; Zhong et al., 2020). Among the different bioactive compounds studied in these type wines, phenolic compounds present an important antioxidant capacity by different ways: reducing agents, hydrogen donators, free radical scavengers, singlet oxygen quenchers, and so forth (Mundaragi & Thangadurai, 2018; De Souza et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, and mainly due to the creation of the National Coordinator of Wine Clubs of Cuba (NCWCC), Cuba has become one of the countries that produce wines from a greater range of raw materials reaching a great international interest. Although the number of publications about fruit wines and rice wines has increased in recent years (Chay et al., 2020; Kosseva et al., 2017; Płotka‐Wasylkaa et al., 2018; Qian et al., 2019; Seixas et al., 2020; De Souza et al., 2018; Sun et al., 2020; Velic et al., 2018; Wu, Xu, Long, Wang, et al., 2015; Wu, Xu, Long, Zhang, et al., 2015; Zhong et al., 2020), no investigation has been conducted to appraise health‐related major components of these Cuban wines. This study, therefore, evaluates the bioactive‐nutritional compounds (mineral elements, amino acids, and total polyphenols content), antioxidant activities (DPPH and ABTS), and the correlation between the selected factors and the samples of Cuban wines with the objective to highlight these unknown wines for production of healthier wine options.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of fermented blueberry beverage on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals was estimated according to the method of Gow-Chin Yen et al [ 30 ]. Diluted samples (40–200 μL) were added to 3 mL of 0.1 mM DPPH solution.…”
Section: Methodsmentioning
confidence: 99%